Hubungan Tingkat Pengetahuan Dan Aktifitas Fisik Dengan Status Gizi Pada Anak Sekolah Dasar 02 Cupak Tangah Di Kota Padang Tahun 2023 - Yusfita, Ermi (CV. ITTC INDONESIA, 2024)
Nutritional problems that occur in elementary school (SD) children, namely stunted growth, decreased intelligence, decreased immune system. In 2022, West Sumatra Province will have 4 malnutrition areas, namely Padang Pariaman Regency, Bukitinggi City, Agam Regency and Padang City, where the prevalence of malnutrition in Padang City is 1.4% and the prevalence of overnutrition is 2.4%. Malnutrition status in children is caused by food intake, physical activity, infectious diseases, parents' education, type of work, parents' income, food availability, eating patterns, and knowledge. This study aims to determine the relationship between the level of knowledge and physical activity and the nutritional status of elementary school children at SDN 02 Cupak Tangah, Padang City in 2023. The research population is all grades 5 and 6 at SDN 02 Cupak Tangah, Padang City with a total population of 167 students. and a sample of 118 people. Computerized data processing using the chi square test. The results showed that 55% of respondents had poor nutritional status, 70.2% of respondents had low knowledge, and 53.4% ​​of respondents had moderate physical activity at SDN 02 Cupak Tangah, Padang City in 2023. There is a significant relationship between knowledge and nutritional status at SDN 02 with p-value= 0.001 and there is a significant relationship between physical activity and nutritional status at SDN 02 with p-value= 0.003.